Antiplasmodial Potentials and GC-MS Analysis of Bioactive Compounds in Methanol and Ethanol Leaf Extracts of Daniellia oliveri - Muazu , Muhammed; Sani , Abdulsalami Mohammed; Dikwa , Karderam Bukar; Dibal , Deborah Madi; Tijani , Kokori Bajeh; Yahaya , Junaidu (Research Advances in Microbiology and Biotechnology Vol. 7, 2023)
The goal of the study was to analyze D. oliveri utilizing qualitative, quantitative, and Gas Chromatography-Mass Spectroscopy (GC-MS) analytical methods to screen for phytochemical components and determine bioactive substances. The information regarding phytochemical compounds are not only supportive for discovery of therapeutic potential, but also have an active contribution towards discovery of new semi-synthetic and synthetic compounds. The identification of bioactive elements required for evaluating the antiplasmodial potentials of methanol and ethanol leaf extracts of Daniellia oliveri (D. oliveri) may be accomplished by qualitative, quantitative, and Gas Chromatography-Mass Spectrometry (GC-MS) analyses. The leaves were collected in Anyigba, Kogi state from which methanol and ethanol extracts were prepared, phytochemical components detected and bioactive compounds determined using GC-MS. Results showed the presence of alkaloid, tannin, reducing sugar, saponin, terpenoid, phenol, cardiac glycosides and flavonoid in the extracts. Phenol showed the highest concentration (46.14 and 43.09 mg/100g) while terpenoid showed the lowest concentration (10.63 and 9.97 mg/100g) in methanol and ethanol extracts respectively. GC-MS analysis revealed the presence of higher components (57) in methanol extract compared to ethanol extract (27). This study provides scientific evidence that methanol may be a better extraction solvent for GC-MS analysis of D. oliveri leaves meant to be used for the determination of antiplasmodial activity than ethanol due to higher components detected in methanol extract compared to ethanol extract.